Introducing Jus ante Bellum as a cosmopolitan approach to humanitarian intervention. (December 2016) - Brown, Garrett Wallace; Bohm, Alexandra
Cosmopolitans often argue that the international community has a humanitarian responsibility to intervene militarily in order to protect vulnerable individuals from violent threats and to pursue the establishment of a condition of cosmopolitan justice based on the notion of a 'global rule of law'. The purpose of this article is to argue that many of these cosmopolitan claims are incomplete and untenable on cosmopolitan grounds because they ignore the systemic and chronic structural factors that underwrite the root causes of these humanitarian threats. By way of examining cosmopolitan arguments for humanitarian military intervention and how systemic problems are further ignored in iterations of the Responsibility to Protect, this article suggests that many contemporary cosmopolitan arguments are guilty of focusing too narrowly on justifying a responsibility to respond to the symptoms of crisis versus demanding a similarly robust justification for a responsibility to alleviate persistent structural causes. Although this article recognizes that immediate principles of humanitarian intervention will, at times, be necessary, the article seeks to draw attention to what we are calling principles of Jus ante Bellum (right before war) and to stress that current cosmopolitan arguments about humanitarian intervention will remain insufficient without the incorporation of robust principles of distributive global justice that can provide secure foundations for a more thoroughgoing cosmopolitan condition of public right.